A case of Bacillus subtilis var. natto bacteremia caused by ingestion of natto during COVID-19 treatment in a maintenance hemodialysis patient with multiple myeloma. Issue 8 (August 2022) - Kato, Ai; Yoshifuji, Ayumi; Komori, Kohji; Aoki, Kotaro; Taniyama, Daisuke; Komatsu, Motoaki; Fujii, Kentaro; Yamada, Kuniko; Ishii, Yoshikazu; Kikuchi, Takahide; Ryuzaki, Munekazu
Abstract: A 70-year-old woman, who started on hemodialysis 7 months before for end-stage renal disease due to diabetic nephropathy and was diagnosed with symptomatic multiple myeloma 1 month before, was admitted to our hospital with critical coronavirus disease 2019 and treated with long-term immunosuppressive therapy such as steroids and tocilizumab. During treatment, Bacillus subtilis was detected in the blood cultures. We could not exclude the association of natto (fermented soybeans) with B. subtilis var . natto, which the patient had been eating every day from 8 days after admission. She was prohibited from eating natto and treated with vancomycin. Later, B. subtilis detected in the blood culture was identified as B. subtilis var. natto, which was identical with those contained in the natto that the patient consumed daily using a next-generation sequencer. Gut dysbiosis due to old age, malignant tumor, diabetes mellitus, end-stage renal disease, and intestinal inflammation caused by severe acute respiratory syndrome coronavirus 2 increased intestinal permeability and the risk of bacterial translocation, causing B. subtilis var . natto bacteremia. Therefore, careful consideration might be given to the intake of fermented foods containing live bacteria in patients with severe immunocompromised conditions.